2016
DOI: 10.1038/srep38222
|View full text |Cite
|
Sign up to set email alerts
|

Serbian Language version of the Modified Checklist for Autism in Toddlers, Revised, with Follow-Up: Cross-Cultural Adaptation and Assessment of Reliability

Abstract: Early detection of Autism Spectrum Disorder (ASD) has proven to be of high significance, however there is a limited availability of ASD screening tools in Serbian language. In this study we aim to translate, assess reliability and, in part, test the applicability of Modified Checklist for Autism in Toddlers, Revised, with Follow-Up (M-CHAT R/F) in Serbian Healthcare environment. We screened 128 children in three primary healthcare centres and 20 children in a tertiary psychiatric center, using M-CHAT R/F trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…This review presented 19 papers, which included 20 studies, as one paper reported on two different studies [ 41 ]. These studies, from 13 nations (Arab [ 42 , 43 ], Hong Kong [ 44 ], Iran [ 7 , 45 ], Israel [ 13 ], Japan [ 46 , 47 ], Korea [ 48 ], Mexico [ 49 , 50 ], Norway [ 51 ], Sir Lanka [ 19 , 52 ], Spain [ 53 ], Sweden [ 54 ], Turkey [ 41 , 55 ] and Serbia [ 56 ]), met the inclusion criteria for this review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This review presented 19 papers, which included 20 studies, as one paper reported on two different studies [ 41 ]. These studies, from 13 nations (Arab [ 42 , 43 ], Hong Kong [ 44 ], Iran [ 7 , 45 ], Israel [ 13 ], Japan [ 46 , 47 ], Korea [ 48 ], Mexico [ 49 , 50 ], Norway [ 51 ], Sir Lanka [ 19 , 52 ], Spain [ 53 ], Sweden [ 54 ], Turkey [ 41 , 55 ] and Serbia [ 56 ]), met the inclusion criteria for this review.…”
Section: Resultsmentioning
confidence: 99%
“…Canal-Bedia et al [ 53 ] Stage 1: Case control Spain Extended Health Centre & Psychiatric N-2480 18–36 months Parents The Spanish Modified Checklist for Autism in Toddlers (M-CHAT) + M-Chat Phone interview Stage 2: Cross sectional N-2055 18–36 months 5. Carakovac et al [ 56 ] Case control Serbian Primary Healthcare & Psychiatric N = 148 Mean age = 22.25–23.53 months Parents The Serbian Modified Checklist for Autism in Toddlers, Revised with Follow-Up (M-CHAT-R/F) 6. Fombonne et al [ 49 ] Case control Mexico Autism Developmental Disorder Clinic Public primary school N = 563 4–13 years Mean age: 8 years Parents and teachers Spanish version of the Social Responsiveness Scale (SRS) 7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…M-CHAT includes a follow-up interview, which clarifies parent questionnaire responses to reduce false positives. M-CHAT has been assessed in multiple independent primary care samples116117 and internationally in multiple languages using validated translations 118119120121122. It is also available as an electronic tablet based version123; this product improves utilization by primary care pediatricians and can be completed by parents online, potentially increasing access by underserved populations 124.…”
Section: Screening and Surveillancementioning
confidence: 99%
“…For these reasons, the EFA estimating the two-factor structure was preferred and reached a moderate fit of the data, χ 2 (1651) = 2940.15, p < 0.001, CFI = 0.79, RMSEA = 0.034 (LO90% = 0.032, HI90% = 0.036). Nineteen items (Items 4,5,6,16,(27)(28)(29)31,32,39,41,(49)(50)(51)(52)(53)(54)(55)(56) were excluded from the subsequent analysis because the factor loadings loaded for two or more factors. After exclusion of those items, the subsequent fourth EFA reached moderate fit of the data, χ 2 (739) = 1185.47, p < 0.001, CFI = 0.92, RMSEA = 0.03 (LO90% = 0.027, HI90% = 0.033).…”
Section: Internal Consistency and Factorial Analysesmentioning
confidence: 99%